1988
DOI: 10.1007/bf00398185
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic patterns of renal carcinoma: An analysis of 687 necropsies

Abstract: The metastatic behaviour of renal cell carcinoma has been studied in a series of 687 necropsies. The observations were consistent with the concept of "metastatic inefficiency", in that in 295 cases, including 25 with renal vein invasion, there were no detectable metastases. In the present series, renal vein involvement was not an important prognostic factor in stage 1 or 2 disease. In 73% of cases without lung metastases there were none in other sites, and in 84% of those with lung metastases there were others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
77
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(82 citation statements)
references
References 25 publications
4
77
1
Order By: Relevance
“…These have all been relatively small-scale studies (Abrams et al, 1950;Weiss et al, 1988;Weiss, 1992;Disibio and French, 2008). However, we may now study these patterns using computational methods on large data sets.…”
mentioning
confidence: 99%
“…These have all been relatively small-scale studies (Abrams et al, 1950;Weiss et al, 1988;Weiss, 1992;Disibio and French, 2008). However, we may now study these patterns using computational methods on large data sets.…”
mentioning
confidence: 99%
“…However, gallbladder metastasis of RCC is seldom detected, being present in 0.58% of autopsies (2). In a review of the literature, we found 15 reported cases of gallbladder metastasis of RCC (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…However, gallbladder involvement in patients with RCC is extremely rare. The gallbladder was identified as a metastatic site in only 4 out of 687 cases (0.58%) in large autopsy reviews (2). Patients with distant metastasis from RCC have a poor prognosis, with a 5-year survival rate of <10% (3).…”
Section: Introductionmentioning
confidence: 99%
“…In an autopsy series of 125 patients with malignant melanoma, nineteen (15%) had MGBs [2] . In an analysis of 687 necropsies of patients with renal cell carcinoma, four cases had MGBs [3] . However, the data available on MGBs are only from autopsy series of certain malignancies such as melanoma or renal cell carcinoma, or reviews of a certain metastatic carcinoma to the GB such as melanoma [6,7] , or in the form of single case reports of tumors such as melanoma [8][9][10][11] , breast cancer [4] , and hepatocellular carcinoma [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Although malignant melanoma [2] and renal cell carcinoma [3] are reported to metastasize to the gallbladder (GB), these data are based on autopsy series of these tumors. Reports on MGBs arising from malignancies other than malignant melanoma and renal cell carcinoma are usually in the form of single case reports [4,5] .…”
Section: Introductionmentioning
confidence: 99%